The impact of electronic procurement on supplier performances in manufacturing companies a case of Rose form Limited - Maiso Solomon (UCU, 2024)
ABSTRACT. The study Assessed the impact of e-procurement implementation on supplier performance in manufacturing companies with a case of Rose Form Uganda Limited. The study also sought to achieve three objectives to examine the role of e-sourcing in improving supplier performance, the role of electronic procurement integration in improving supplier performance. And analyze the relationship between e-procurement adoption and supplier performance at Rose Form Industries Limited. The ultimate goal was to provide strategic insights for the impact of e-procurement development, e-sourcing on supplier performances. To enhance digitalization of organizational procurement practices and stimulate further scholarly inquiry. The Research Methodology employed a mixed-methods approach, integrating qualitative and quantitative techniques. Simple Random sampling strategy was used to select 36 participants from a population of 40 with a focus on different individuals within the Organization. Data collection involved primary sources such as interviews, questionnaires and observations, supplemented by secondary sources. The also research aimed to stringent procedures to ensure precision and prioritized research objectives to effectively navigate limitations such as time constraints, information silos and limited resources The analysis found out a predominantly Male participant group with diverse educational backgrounds, age distribution and length of service at Rose Form Uganda Limited. There was substantial support for e-procurement practices, e-sourcing tools like e-catalogs, e-ordering, erequisition’s. The survey findings revealed varying perspectives that e-sourcing tools are effective in improving supplier identification, productivity, and sales processes, with a significant percentage of respondents affirming their benefits. E-procurement practices also showed significant improvements in procurement efficiency, supplier selection, and delivery scheduling, supported by relatively high positive responses from the respondents. Despite the overall positive impact, there are mixed opinions regarding e-procurement's effect on procurement cycle times and error reduction. The study findings highlighted the need for improved customization, error detection, and operational integration, providing recommendations for enhancing e-procurement practices and supplier relationships. Like enhancing Customization and Training for E-Sourcing Tools, Improving Error Detection and Address Discrepancies in E-Procurement Systems, Strengthening Supplier Relationship Management and Transparency Initiatives and Monitoring, Evaluating the Impact of E-Procurement on Operational Efficiencies with in organizational operations which contributed to valuable insights into optimizing procurement processes and advancing the understanding of e-procurement in business management.